Effects of Different Weeding Methods on Soil Physicochemical Properties, Root Morphology, and Fruit Economic Traits in Camellia oleifera Abel. Plantations - Xueyun Shi; Huaiyuan Wu; Shuangling Xie; Hongkui Li; Yan Wang; Yuman Wang; Huiyun Liu; Qinhua Cheng; Zongde Wang; Dongnan Hu (Horticulturae)
Soil physicochemical properties, root characteristics, and fruit economic traits were determined in Camellia oleifera plantations under spontaneous vegetation + mowing (W1), spontaneous vegetation + glyphosate (W2), and no weeding (CK) treatments. Compared with CK, W1 reduced soil bulk density and increased total nitrogen, total phosphorus, ammonium nitrogen, nitrate nitrogen, and effective potassium content. W2 treatment resulted in higher bulk density than W1 and lower water-holding capacity, total nitrogen, total phosphorus, total potassium, ammonium nitrogen, nitrate nitrogen, and available potassium of the soil. Generally, both W1 and W2 inhibited weed morphological traits while favoring the C. oleifera root system, with the W1 treatment resulting in the greatest increase. Fruit transverse diameter, longitudinal diameter, yield, and oil yield were higher in W1 than in CK and W2 treatments. Weed root systems and C. oleifera root systems ultimately affect oil production and yield by affecting bulk density, ammonium nitrogen, nitrate nitrogen, fruit transverse diameter, seed yield, and seed kernel oil content. In summary, W1 treatment improved the physicochemical properties, root growth, fruit growth, and soil quality in C. oleifera plantations.